Pemikiran Haji Agus Salim tentang Aqidah, Sharîah, dan Ideologi - Moh. Qoyyim (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2013)
This article discusses the thinking of Haji Agus Salim about aqîdah, sharî‘ah, and Ihsân. Regarding the Agus Salim’s thinking about Aqeedah, he covers the concept of tawhîd (the deity), destiny (God’s provision) and resignation (surrender). While thinking associated with sharî‘ah contains ideas in social and ritual. The idea of charity was oriented at a picture of the attitudes and virtues in Islam that applied. Haji Agus Salim patterns of thought very dialectic and dynamic that unites the mind with the teachings of Islam as well as enriched with actual discourse and historical dimensions.